2009
DOI: 10.3109/02713680903395281
|View full text |Cite
|
Sign up to set email alerts
|

Nasal-Associated Lymphoid Tissue Is Not an Absolute Requirement for the Induction of Rat Tear IgA Antibody Responses

Abstract: These results indicate that particulate antigen can be taken up by the conjunctiva and transported to the draining lymph nodes, showing that antigen does not need to access nasal-associated lymphoid tissue to induce tear IgA antibody responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…46 These events can occur in the eye associated lymphoid tissues ( EALT ), such as those present in the conjunctiva or lacrimal glands. 47 In pioneering experiments, Allansmith et al showed that the exposure of germ-free rats to the conventional environment resulted in a significant increase in the number of IgA- and IgM-producing B cells in the lacrimal glands. The conventionalization of the germ-free rats took four weeks at which point the tear levels of secretory IgA in the ex-germ-free rats reached levels comparable to those of the regular rats.…”
Section: What Is the Impact Of The Microbiome On Ocular Immunity?mentioning
confidence: 99%
“…46 These events can occur in the eye associated lymphoid tissues ( EALT ), such as those present in the conjunctiva or lacrimal glands. 47 In pioneering experiments, Allansmith et al showed that the exposure of germ-free rats to the conventional environment resulted in a significant increase in the number of IgA- and IgM-producing B cells in the lacrimal glands. The conventionalization of the germ-free rats took four weeks at which point the tear levels of secretory IgA in the ex-germ-free rats reached levels comparable to those of the regular rats.…”
Section: What Is the Impact Of The Microbiome On Ocular Immunity?mentioning
confidence: 99%
“…Likewise, herpes simplex virus in human tears has been shown to flow through the lacrimal canaliculi into the nasal cavity (Yoshida and Hondo, 1992); (2) intranasal, oral, or gastric administration of bacteria, viruses, or other antigens may induce the accumulation of specific tear IgA antibodies and the generation of ocular surface protection (Mestecky et al, 1978;Nichols et al, 1978;Montgomery et al, 1983Montgomery et al, , 1984aBergmann et al, 1986;Waldman and Bergmann, 1987;Czerkinsky et al, 1987;Van Zaane et al, 1987;Peppard et al, 1988;Peppard and Montgomery, 1990;Davidson et al, 1993;Carr et al, 1996;Noriega et al, 1996;Montgomery and Rafferty, 1998;Ridley Lathers et al, 1998;Gill and Montgomery, 2002). On the other hand, recent studies now indicate that particulate antigen can be taken up by the conjunctiva and transported to the draining lymph nodes, showing that NALT is not an absolute requirement for the induction of rat tear IgA responses (Gill et al, 2010).…”
Section: Response To Defined Antigensmentioning
confidence: 92%
“…The T-lymphocyte-dependent pathway is through the interaction of antigen-specific B lymphocytes with CD4+ T lymphocytes. This interaction occurs in the eye conjunctiva and lacrimal glands (43). It is important for normal rats to reach IgA and IgM levels of germ cell-free rats in the lacrimal glands 4 weeks after exposure to environmental factors, suggesting that the local immunity may interact with the ocular flora leading to a direct effect (44).…”
Section: Relation Of Ocular Immunity With Ocular Microbiotamentioning
confidence: 99%